Orobothriurus atiquipa, a new bothriurid species (Scorpiones) from Lomas in southern Perú - Ochoa, José Antonio (2002)
Orobothriurus atiquipa new species (Scorpiones, Bothriuridae) from Lomas formations in the coastal desert of southern Perú is described and illustrated. This species belongs to the alticola species-group, and within the group, it is closely related to O. alticola (Pocock), O. paessleri (Kraepelin) and O. curvidigitus (Kraepelin). The spine formula (4 + 3) on tarsi III–IV is probably an autapomorphy for the new species. Some features of the habitat (the Lomas formation are green isolates in the coastal desert), as well as a distribution map are provided.